Hubungan Kerja Sama Antara Guru Dan Orang Tua Dalam Meningkatkan Motivasi Belajar Siswa Kelas V-C Di UPT SD Negeri 220 Gresik - Riki Adi Setiawan; Pristiwiyanto Pristiwiyanto (THE JOER: Journal Of Education Research, 2023)
This study aims to determine the cooperative relationship between teachers and parents in increasing student motivation. This type of research is quantitative correlation. The population in this study were 33 students in class V-C at UPT SD Negeri 220 Gresik. Data collection techniques in the form of documentation, interviews, and scales. The analysis technique used is the product moment correlation technique with the results of the research showing that there is a correlation from the cooperative relationship between teachers and parents in increasing student learning motivation. The form of a cooperative relationship between teachers and parents that is implemented at UPT SD Negeri 220 Gresik includes meeting activities that discuss learning, problems with students, and development at school. In addition, there is a form of communication that is carried out through group forums for class V-C associations. Communication is carried out to exchange information between the school and parents regarding learning problems in students so that they can be solved together. Based on the test results through the statistical package for social science (SPSS) on a scale of cooperative relations between teachers and parents with 15 question items having an average value of 70.79 with a very high rating score category. On the learning motivation scale with 10 question items, it has an average of 46.52 with a high rating score category. To determine the existence of a correlation in a data, it can be stated that if the data has a value of <0.05 then there is a correlation, and if the data is > 0.05 then there is no correlation. These results are evident from the results of the significance of 0.000 <0.05 so that the hypothesis can be stated that there is a correlation of the cooperative relationship between teachers and parents in increasing student learning motivation at UPT SD Negeri 220 Gresik.